Classic Children's Books Collection - Grahame, Kenneth (Saga Egmont, 2024)
Dive into this joyous collection of classical children’s books from some of the best writers for little hearts and young minds. Uncover the magic of childhood classics from ´Anne of Green Gables´, ´The Wind in the Willows´, and ´The Secret Garden´ to ´The Velveteen Rabbit´ and ´The Wonderful Adventures of Nils´. Follow one girl's search for belonging, go on thrilling adventures with our favourite furry friends, discover a magical garden, learn about love and reality with a toy rabbit, and join one boy as he embarks on fantastical farmland adventures! Weaving a touching and intoxicating collection of coming-of-age tales, this ‘Classic Children's Books Collection’ is the perfect companion for fans of Netflix’s ‘Anne with an E’. Lucy Maud Montgomery (1874-1942) was a Canadian author and poet. Best known for her novel ‘Anne of Green Gables’, it remains one of the best-selling books worldwide and has been adapted for both stage and screen. Kenneth Grahame (1859-1932) was a British writer born in Edinburgh, Scotland. He is most famous for the children’s classics ‘The Wind in the Willows’ and ‘The Reluctant Dragon’. Frances Hodgson Burnett (1849-1924) was a British-American novelist and playwright. Best known for her celebrated children’s novels, Burnett’s work spans ‘Little Lord Fauntleroy’, ‘A Little Princess’, and ‘The Secret Garden’. Selma Lagerlöf (1858-1940) was a Swedish author and the first woman to win the Nobel Prize in Literature. Her work spans ‘The Saga of Goesta Berling’, ‘The Wonderful Adventures of Nils Holgersson’, and ‘Jerusalem’.